Gap symmetry and charge density excitations in high-Tc superconductors with extended saddle points in electron spectrum - Pashitskii, E.A.; Pentegov, V.I.; Semenov, A.V. (Condensed Matter Physics, 1999)
It is shown that the strong anisotropy of the one-particle electron spectrum,
due to the presence of extended saddle-point features (ESPF) close to the
Fermi level in the hole-type cuprates YBCO and BSCCO, leads to the occurrence of a low-frequency peak in the spectral function of the charge
density ﬂuctuations due to the presence of acoustic plasmon branch in the
collective electron spectrum. The retarded anisotropic electron-plasmon interaction leads to the suppression of the static screened Coulomb repulsion
for small transferred momenta and, consequently, to the effective attraction
between electrons in the dx²-y²-wave channel of the Cooper pairing of
current carriers. Breaking of C₄v symmetry in YBCO crystals leads to a
possibility of a change of dx²-y²-wave symmetry of the gap to a mixed
s − d gap symmetry for singlet Cooper pairs or to a p-wave gap symmetry
for triplet pairs. Показано, що сильна анізотропія одночасткового електронного
спектру веде, завдяки наявності подовжених сідлових особливостей
біля рівня Фермі у купратах YBCO та BSCCO, до появи низькочастотного піку у спектральній функції флуктуацій зарядової густини, що
є наслідком присутності гілки акустичних плазмонів у колективному
електронному спектрі. Електрон-плазмонна взаємодія веде до значного зменшення статичного кулонівського відштовхування в області малих переданих імпульсів та, як наслідок, до ефективного притягнення між електронами у dx²-y²-хвильовому каналі куперівського спарювання носіїв струму. Порушення C₄v симетрії у кристалах
YBCO призводить до можливості заміни dx²-y²-хвильової симетрії
надпровідної щілини на змішану s − d симертрію для сінглетних куперівських пар або на p -хвильову симетрію щілини для триплетних
пар.